Transnational Narcotics Trafficking and the Role of NCB Interpol Indonesia: A Case Study from West Java - Aulia, Yolanda Putri; Rifai, Maulana; Marsingga, Prilla (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to examine the role of the National Central Bureau (NCB) Interpol Indonesia in addressing transnational narcotics crimes in West Java Province between 2020 and 2023. With the increasing complexity of international drug trafficking networks, effective international cooperation becomes essential. This research employs a normative juridical approach with qualitative methods, drawing from primary and secondary legal materials including regulations, reports, and interviews. The findings reveal that the NCB Interpol plays a crucial coordinating role in cross-border law enforcement, particularly through mechanisms such as Red Notices, intelligence sharing, and coordination with domestic institutions including BNN and the National Police. Despite the progress made, challenges such as legal harmonization, jurisdictional issues, and technological barriers still hinder optimal cooperation. Strengthening legal frameworks and enhancing technical capacities are recommended to improve the effectiveness of transnational narcotics crime suppression.